Purification and characterization of arginine deiminase from Klebsiella pneumoniae - Taif Hussien Alameedy; Mohammed Abdullah Jebor (Medical Journal of Babylon)
Abstract Background and Objectives: This study was aimed to characterize arginine deiminase (ADI) purified from Klebsiella pneumoniae in vitro. Materials and Methods: Precipitation with 70% saturated ammonium sulphate, ion exchange chromatography with a DEAE-cellulose column, and gel filtration chromatography throughout sepharose-6B were the three steps taken to isolate the arginine-degrading enzyme from a K. pneumoniae clinical isolate, which is a potent anticancer source. Results: After 5.9 folds of purification and 38.7% enzyme recovery, the specific activity of the purified enzyme reached 164.2 U/mg. When biochemical characteristics of the purified enzyme were studied, results showed that the activity was maximum at pH 6 and is most stable in pH ranging from (5–9), the optimum temperature for enzyme activity was observed at 37ºC and reach 11.5 U/mL. In contrast, ethylenediaminetetraacetic acid (EDTA), NaNO3, and ZnSO4 slightly inhibited ADI activity, whereas MnCl2, increased the remaining activity of enzyme to 125%., as well as NaNO3, EDTA, ZnSO4, and FeCl3 were found that they inhibit enzyme activity by 90, 70, 88, and 110, respectively. Conclusion: A locally isolated strain of K. pneumoniae N1 is a useful and potent arginine deiminase producer.